Composition and Structure of Oil Finishing Agent † - Indra Neel Pulidindi (International Journal of Crystalline Materials, 2024)
Use of oil finishing agent is widely used in the process of production of carbon fibers to impart unusual and exceptional strength to the carbon fibers, the key load-bearing component, of the advanced materials, namely, carbon fiber reinforced composites (CFRPs). CFRPs are being widely used in the realm of aeronautics, astronautics, aeronautics, geonautics, sports equipment, and many more. However, quite often, much of the knowledge on the composition of oil finishing agents is concealed owing to the commercial relevance of the material. The subject of the chemical composition of oil finishing agents is seldom found in open literature as it is a proprietary material. Oil finishing agent imparts excellentstrengthh to carbon fibers. The oil finishing agent mainly comprises three components, namely, the epoxy/amino polyether-modified silicone, a non-volatile compound (diluent), and a surfactant. Characterization and analysis of the composition of oil agents are complicated and even experienced chemists are misleading owing to the ingenuity with which the oil finishing agent is formulated. NMR (1H, 13C, and 29Si) and FT-IR spectroscopy were judiciously used to find that the oil finishing agent is composed of lactic acid (3H, d; 0.81 and 1.21 ppm); formate type anions (1H, s; 8.3 ppm); organic silicone compounds [epoxy polyether-modified silicone; hexamethyldisilazane (HMDS)], a unique and unconventional methanol –dioxane complex used as a non-volatile solvent or diluent (dioxane also serves as surfactant). The presence of four characteristic signals at – 109.12, -22.42, - 19.6,2, and 7.17 ppm in the 29Si NMR spectrum of thoil-finishing agent indicated the presence of Si in four different chemical environments in the form of hexamethyl disiloxane (HMDS) and epoxy polyether-modified silicone. Such a result is further supported by the 1H NMR, 13C NMR, and FT-IR studies. Thus the mysterious chemical composition of the oil finishing agent is disclosed.
Keywords: FT-IR; NMR; Oil finishing agent; diluent; epoxy polyether modified poly organo siloxanes; lactic acid; methanol – dioxane complex; oil agent